2014
DOI: 10.1021/ja410747g
|View full text |Cite
|
Sign up to set email alerts
|

WMe6 Tamed by Silica: ≡Si–O–WMe5 as an Efficient, Well-Defined Species for Alkane Metathesis, Leading to the Observation of a Supported W–Methyl/Methylidyne Species

Abstract: The synthesis and full characterization of a well-defined silica-supported ≡Si-O-W(Me)5 species is reported. Under an inert atmosphere, it is a stable material at moderate temperature, whereas the homoleptic parent complex decomposes above -20 °C, demonstrating the stabilizing effect of immobilization of the molecular complex. Above 70 °C the grafted complex converts into the two methylidyne surface complexes [(≡SiO-)W(≡CH)Me2] and [(≡SiO-)2W(≡CH)Me]. All of these silica-supported complexes are active precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
160
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(172 citation statements)
references
References 56 publications
10
160
0
2
Order By: Relevance
“…218 In a related example a polymethyl tungsten complex anchored to a silica surface leads to W-methyl/methylidyne species upon heating due to double α-hydrogen abstraction (Scheme 37c). 219 Related to this, metal-bound methyl mediated α-and β-hydrogen abstraction from amides 220 and cyclopropyl 221 ligands, respectively, with concomitant liberation of methane have also been documented. TM-CH3 complexes can rearrange by reversible α-hydrogen elimination and formation of (H)TM=CH2 species (Scheme 37d).…”
Section: Protonolysis and Hydrogenolysismentioning
confidence: 89%
“…218 In a related example a polymethyl tungsten complex anchored to a silica surface leads to W-methyl/methylidyne species upon heating due to double α-hydrogen abstraction (Scheme 37c). 219 Related to this, metal-bound methyl mediated α-and β-hydrogen abstraction from amides 220 and cyclopropyl 221 ligands, respectively, with concomitant liberation of methane have also been documented. TM-CH3 complexes can rearrange by reversible α-hydrogen elimination and formation of (H)TM=CH2 species (Scheme 37d).…”
Section: Protonolysis and Hydrogenolysismentioning
confidence: 89%
“…[9] In the following work, we envisage that employing a single multifunctional silica-supported catalyst 1 would be an alternative catalytic system for the synthesis of a wider distribution of macrocyclic alkanes (Figure 1). [10] We report here our findings showing remarkable results on cycloalkane metathesis with this W catalyst.…”
Section: Introductionmentioning
confidence: 72%
“…[16] The supported pre-catalyst [(SiO)W(Me) 5 ] 1 was prepared according a literature report. [10] NMR spectra were recorded on Bruker 500 and 600 MHz instruments. ), 300 8C (30 min); Cyclic alkanes retention time: t R (cyclooctane): 6.51 min, t R (cyclohexadecane, dimer): 13.56 min, t R (cyclotetraeicosane, trimer): 19.30 min.…”
Section: Experimental Section General Considerationsmentioning
confidence: 99%
“…Handling this compound is challenging due to its explosive nature as reported by Shortlan and Wilkinson [1,2], Galyer et al [3], Galyer and Wilkinson [4]. In our previous communication, we demonstrated that grafting this unstable WMe 6 to the silica surface by SOMC (Surface OrganoMetallic Chemistry) strategy and methodology at À80°C can enhance its thermal stability due to the formation of the stable grafted complex, [SiO-W(Me) 5 ] which proved to be a nice precursor of alkane metathesis catalysts via the formation of surface monopodal tungsten carbyne [11]. This carbyne is in equilibrium with a bis carbene upon addition of a donor ligand [12] (Scheme 1).…”
Section: Introductionmentioning
confidence: 89%